Mechanical Properties of Hybrid Pineapple Leaf and Kenaf Fibers Composite - Wan Hashim, Wan Amin Khalili; Ariffin, Ahmad Hamdan; Zulkafli, Mohd Fadhli (Progress in Aerospace and Aviation Technology, 2024)
The use of natural fibers such as pineapple leaf (PALF) and kenaf fibers in composite materials has gained attention due to their potential to provide improved mechanical properties over traditional materials. Furthermore, there is significant opportunity for this idea to be employed in high-value sectors like building, aircraft, and automobiles. Therefore, the study aims to investigate the mechanical properties of hybrid kenaf fibers and PALF composite material for aircraft applications. The hybrid composite ratio between kenaf fiber and PALF varies into three different ratios. The kenaf fiber:PALF ratio is 60:40, 40:60, and 50:50, respectively. The samples were fabricated via a hand-layup process. Tensile and flexural testing were conducted to analyze the mechanical properties of the hybrid composite. The Scanning Electron Microscope (SEM) was employed to investigate the structure morphology. The tensile testing shows that the 40:60 ratio composite has the highest maximum stress (69.14 MPa). Besides that, the 60:40 ratio composite has the maximum flexural strength (129.35 MPa). The SEM investigation reveals that the failure occurs due to matrix deformation, fiber breaking, and fiber pullout. The results show that the hybrid composite has good performance as compared to the existing material in aviation, such as for food trays, inner walls, and low-critical composite parts. Hence, it has a big potential for further enhancement with regards to weight reduction, increasing fuel efficiency, and lowering carbon emissions in the aviation sector.